Avaliação de diferentes rotas de encapsulamento de aromas em nanofibras poliméricas - Brichi, Glaucia Silveira (Universidade Federal de São Carlos, 2016)
The use of flavor has become increasingly common in the food and pharmaceutical industry, including menthol and ethyl hexanoate (EH) (main ester passion fruit aroma) has achieved prominence in the industry due to its applications ranges in branches different sectors. Among the various properties that flavorings have, the main one is the volatility and the ease of leaving the environment. In this sense, there is a great interest to seek new mechanisms to increase the aromas of residence time in the array. The present work, looking for encapsulating the aromas of mint and hexanoate Ethyl (EH), through polymeric nanofibers, also studied the influence in the tunnel when the β-cicldodextrin is added to the solution and when the fibers are obtained by different routes electrospinning and spinning blow solution (FSS).After obtaining the polymeric fibers of poly (lactic acid) (PLA) by electrospinning and solution blow spinning techniques, the fibers were characterized by Scanning Electron Microscopy (SEM),Ray Diffraction (XRD), Vibrational Spectroscopy Absorption Infrared (FTIR) spectroscopy, differential scanning calorimetry (DSC) and thermogravimetry (TG / DTG). The release profile was performed for all conditions studied aromas. The results showed the polymer nanofibers, a promising tool for encapsulation of flavorings, may be enhanced by the cyclodextrin. The Solution blow spinning (SBS) techniques and electrospinning were effective to form fibers. SBS methodology originated more homogeneous samples with smaller diameters and without the presence of beads.
Evaluation of different routes of flavors encapsulation into polimeric nanofiber
Keywords: Encapsulamento; Nanofibras; Aromar; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA